Regulação da expressão do receptor AT2 e efeito da angiotensina II sobre a expressão de genes envolvidos no desenvolvimento folicular e ovulação em células da granulosa de bovinos - Portela Junior, Valério Valdetar Marques (2007)
The objective of this study was to investigate the factors controling the expression of angiotensin II (AngII) receptors and to determine the physiological role of AngII in granulosa cells. The AGTR2 receptor was localized in granulosa (and theca) cells from follicles of different sizes. Bovine ovaries were collected at a local abattoir and small follicles (2-5mm) were isolated for harvesting granulosa cells. The cells were cultured in free medium serum in non-luteinizing conditions without FSH (control group) or with graded doses of FSH or IGF1. In other cultures, cells were cultured with or without IGF1 and bone morphogenetic protein-7 (BMP-7), and fibroblast growth factor-2 (FGF-2). Treatment with FSH, IGF1 and BMP-7 increased (P<0.05) estradiol secretion and AGTR2 mRNA expression relative to control cultures. In contrast, none of these treatments affected AGTR1 receptor expression. Addition of FGF-2 significantly decreased estradiol secretion but did not affect AGTR1 or AGTR2 expression. Cells were cultured with FSH plus graded doses of FGF-7 or FGF-10, and the effects of these factors on AGTR2 protein levels were measured by Western blot. AGTR2 protein levels decreased in the groups treated with FGF-7 (10 and 100ng/ml) and FGF-10 (all concentrations; P<0.05), and estradiol secretion was significantly inhibited by the highest dose of each FGF (P<0.05). Bovine follicles greater than 5 mm diameter were dissected and granulosa and theca cells were separated for RNA extraction, and follicle fluid assayed for estradiol (E2) and progesterone (P) content. Non-atretic follicles (P less than 100ng/ml) were classed as estrogenic (E2 greater than 100ng/ml) or non-estrogenic (E2 less than 40ng/ml). There were no differences in AGTR1 receptor expression in theca and granulosa cells between estrogenic and nonestrogenic follicles. Likewise, there were no changes in AGTR2 receptor expression in theca cells with follicle state. However, AGTR2 receptor mRNA levels were significantly higher in granulosa cells of estrogenic compared to non-estrogenic follicles (P<0.01), and AGTR2 receptor mRNA was correlated with E2 concentrations in follicular fluid. To determine the physiological consequences of AT activation in granulosa cells, cells from small (2-5mm) bovine follicles were cultured in serum-free medium with FSH ± AngII. The addition of AngII had no effect on estradiol or progesterone secretion, but significantly inhibited protease nexin-1 (PN-1) mRNA levels and protein secretion (P<0.05). PN-1 is an inhibitor of proteases involved in extracellular matrix remodeling and follicle rupture. Bovine granulosa cells from large (>10 mm) follicles were cultured for 6h, 12h and 24h with LH (100ng/ml) or AngII, with or without angiotensin receptor blocker (losartan for AGTR1 and PD123,319 for AGTR2). These cells expressed Ptgs2 under basal culture conditions, which was not upregulated by either LH or AngII alone. However, LH and AngII in combination significantly enhanced Ptgs2 (P<0.05) mRNA and protein accumulation. Similarly, expression of the proteolytic enzymes uPA and tPA, and their inhibitor, PN-1, were upregulated by the combination of LH and AngII but not by either factor alone. The addition of AGTR blockers inhibited the effect of AngII. In conclusion, AGTR2 receptor is present in granulosa bovine cells, and mRNA and protein are regulated by FSH, IGF-1, BMP-7, FGF-7 and FGF-10 in bovine granulosa cells in vitro, AGTR2 but not AGTR1 receptor mRNA levels are regulated during follicular growth in cattle, and that AngII regulates granulosa PN-1 secretion. These data suggest that AngII is a physiological co-factor necessary for the expression of genes in granulosa cells that are critical for ovulation.